Rare heterochronous liver and pancreatic multiple primary cancers: a case report and literature review - Zhang, Wangjun; Xiao, Fan; Li, Jie; Guo, Xiaoyu; Lin, Zhitao; Huang, Zijian; Mao, Ning; Sun, Bei; Wang, Gang (Zeitschrift für Gastroenterologie, 2020)
In recent years, with the continuous improvement of medical diagnostic techniques, the incidence of multiple primary carcinoma (MPC) has increased gradually. Elderly patients are at high risk of MPC. However, the risk of developing a second primary malignancy is 1 % for primary liver malignancy 1. The risk of pancreatic cancers as secondary malignancies with primary liver malignancy is very rare. Here, we report a rare case of heterochronous liver and pancreatic MPCs and review the related literature. We report this case to raise the clinician’s attention to the disease because the long-term survival rate can be effectively improved by timely diagnosis and appropriate treatment. For patients with HCV-positive primary cancers, active antiviral therapy should be simultaneously provided with antitumor therapy, thereby effectively reducing the incidence of MPC.
Keywords: multiple primary carcinoma; pancreatic cancer; liver cancer; HCV; diagnosis; treatment